MOFs as Multifunctional Catalysts: Synthesis of Secondary Arylamines, Quinolines, Pyrroles, and Arylpyrrolidines over Bifunctional MIL-101 - Cirujano, Francisco G.; Leyva-Pérez, Antonio; Corma, Avelino; Llabrés i Xamena, Francesc X. (ChemCatChem, 2013)
Bifunctional MIL‐101 MOFs containing Lewis acid Cr3+ sites and Pd or Pt hydrogenation/reduction centers, either as isolated metal complexes or in the form of encapsulated metal nanoparticles, have shown to be highly active catalysts for the one‐pot nitroarene reduction and reductive amination of carbonyl compounds. This preparation procedure has been successfully applied to the synthesis of secondary arylamines, quinolines, pyrrols, and 3‐arylpyrrolidines. In all the cases, the MOFs have shown superior performances with respect to commercially available Pd and Pt metal catalysts under the same conditions. Site‐seeing with MOFs: Bifunctional MIL‐101 MOFs containing Lewis acid Cr3+ sites and Pd or Pt hydrogenation/reduction centers are highly active catalysts for the one‐pot conversion of nitro compounds into valuable nitrogen containing chemicals.